Exploring Racial Violence During the Gilded Age and Progressive Era: A Microsyllabus Project. (October 2021) - Lansing, Michael; Cortez, Jonathan; Jacobs, Aaron; Legg, John; Stamilio, Anthony; Tyler-Wolfe, Jae
Abstract : The police murder of George Floyd in Minneapolis in May 2020 (just twenty-two city blocks from where I write) sparked global demonstrations and renewed long-standing struggles for change. At the southern border, government agents separated migrant children from their families and confined detainees in cages. Politicization of the pandemic made Asian Americans targets of violent racist outbursts. Indigenous women continued to suffer disproportionate harm with little attention to their plight. Finally, the right-wing insurrection at the U.S. Capitol in Washington, DC, in January 2021 marked the moment as especially volatile.